Evidence of Glycolysis Up-Regulation and Pyruvate Mitochondrial Oxidation Mismatch During Mechanical Unloading of the Failing Human Heart: Implications for Cardiac Reloading and Conditioning - Diakos, Nikolaos A. (JACC Basic Transl Sci, 2016)
This study sought to investigate the effects of mechanical unloading on myocardial energetics and the metabolic perturbation of heart failure (HF) in an effort to identify potential new therapeutic targets that could enhance the unloading-induced cardiac recovery. The authors prospectively examined paired human myocardial tissue procured from 31 advanced HF patients at left ventricular assist device (LVAD) implant and at heart transplant plus tissue from 11 normal donors. They identified increased post-LVAD glycolytic metabolites without a coordinate increase in early, tricarboxylic acid (TCA) cycle intermediates. The increased pyruvate was not directed toward the mitochondria and the TCA cycle for complete oxidation, but instead, was mainly converted to cytosolic lactate. Increased nucleotide concentrations were present, potentially indicating increased flux through the pentose phosphate pathway. Evaluation of mitochondrial function and structure revealed a lack of post-LVAD improvement in mitochondrial oxidative functional capacity, mitochondrial volume density, and deoxyribonucleic acid content. Finally, post-LVAD unloading, amino acid levels were found to be increased and could represent a compensatory mechanism and an alternative energy source that could fuel the TCA cycle by anaplerosis. In summary, the authors report evidence that LVAD unloading induces glycolysis in concert with pyruvate mitochondrial oxidation mismatch, most likely as a result of persistent mitochondrial dysfunction. These findings suggest that interventions known to improve mitochondrial biogenesis, structure, and function, such as controlled cardiac reloading and conditioning, warrant further investigation to enhance unloading-induced reverse remodeling and cardiac recovery.